2021
DOI: 10.3390/jcm10194362
|View full text |Cite
|
Sign up to set email alerts
|

Complete Purging of Ewing Sarcoma Metastases from Human Ovarian Cortex Tissue Fragments by Inhibiting the mTORC1 Signaling Pathway

Abstract: Restoration of fertility by autologous transplantation of ovarian cortex tissue in former cancer patients may lead to the reintroduction of malignancy via the graft. Pharmacological ex vivo purging of ovarian cortex fragments prior to autotransplantation may reduce the risk of reseeding the cancer. In this study we have investigated the capacity of Everolimus (EVE), an inhibitor of the mammalian target of rapamycin complex 1 (mTORC1) signaling pathway, to eradicate Ewing’s sarcoma (ES) from ovarian tissue by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 65 publications
(98 reference statements)
0
1
0
Order By: Relevance
“…In recent years, a multitude of strategies have been employed to eradicate tumor cells within ovarian tissue [ 97 , 240 , 241 ], the light-dependent nature of PDT suggests its potential safety superiority over other methods. Even if the photosensitizing agent remains in the body after transplantation, PDT is not toxic to the organism.…”
Section: Role Of Nanoregulators In Ovarian Tissue Cryopreservation An...mentioning
confidence: 99%
“…In recent years, a multitude of strategies have been employed to eradicate tumor cells within ovarian tissue [ 97 , 240 , 241 ], the light-dependent nature of PDT suggests its potential safety superiority over other methods. Even if the photosensitizing agent remains in the body after transplantation, PDT is not toxic to the organism.…”
Section: Role Of Nanoregulators In Ovarian Tissue Cryopreservation An...mentioning
confidence: 99%
“…Ovarian autotransplantation is performed when a patient has fully recovered from disease, but this approach may carry a small risk of reintroducing malignant cells in patients with cancer. 42 The results of some studies have suggested that the risk of reintroducing malignant cells could be minimised by meticulous examination of representative biopsy samples via histology, immunohistochemistry, and molecular biology techniques. 43 Moreover, optical coherence tomography can be used to assess malignant cells in thawed ovarian tissue before transplantation.…”
Section: Current Status Of Ovarian Tissue Transplantationmentioning
confidence: 99%